Electron localization properties in high pressure hydrogen at the liquid-liquid phase transition by Coupled Electron-Ion Monte Carlo. (December 2018) - Pierleoni, Carlo; Rillo, Giovanni; Ceperley, David M.; Holzmann, Markus
Abstract: We analyze in detail the electronic properties of high pressure hydrogen around the liquid-liquid phase transition based on Coupled Electron-Ion Monte Carlo calculations. Computing the off-diagonal single particle density matrix and the momentum distribution we discuss localization properties of the electrons. The abrupt changes of these distributions indicate a metal to insulator transition occurring together with the structural transition from the atomic to molecular fluid. We further discuss the electron-proton and electron-electron pair correlation functions, which also change abruptly at the transition.